Strategi Digital Marketing dalam Meningkatkan Daya Saing Namira Islamic School - Uswatun Hasanah; Sugiharto Pujangkoro; Beby Karina Fawzeea Sembiring (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The increasing competition among private educational institutions requires schools to adopt effective marketing strategies to enhance competitiveness and attract public interest. The development of digital technology has shifted marketing practices from conventional approaches to digital-based strategies. This study aims to analyze the digital marketing strategies implemented by Namira Islamic School in improving its competitiveness, as well as to identify supporting and inhibiting factors in their implementation. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, documentation, and focus group discussions involving school management, marketing communication staff, students, and parents. The findings indicate that Namira Islamic School utilizes various digital marketing channels, including websites and social media platforms such as Instagram, Facebook, and YouTube, to promote school programs, activities, and achievements. However, the implementation of digital marketing has not been fully optimized due to limited human resources, unstructured content management, and the absence of comprehensive digital marketing planning. Digital marketing contributes positively to increasing school visibility and public awareness, which supports competitiveness. This study implies that educational institutions need structured digital marketing strategies, competent human resources, and consistent content management to strengthen competitiveness in the digital era.